The Effect of Hybrid Fibers on Some Properties of Structural Lightweight Self-Compacting Concrete by using LECA as Partial Replacement of Coarse Aggregate - Ali, Salah Mahdi; Awad, Hadeel K. (Engineering, Technology & Applied Science Research, 2024)
Self-Compacting Concrete (SCC) is a concrete with high workability. It fills the molds and passes between the narrow openings of reinforcing steel bars without the need for any mechanical pressure or compaction and without the need of a vibrator. Structural Lightweight Self Compacting Concrete (SLWSCC) is an innovative concrete developed in recent years. This concrete type combines the characteristics of lightweight concrete and SCC. This study focused on preparing the appropriate mixture to obtain SLWSCC by using Lightweight Expanded Clay Aggregate (LECA) as a volumetric partial replacement of coarse aggregate by 20, 40, 60, and 80%, reinforced by volumetric ratios of single and hybrid Micro steel Fiber (MF) and Hooked steel Fiber (HF( of 1.5 MF, 0.75 HF+0.75 MF, 1 HF+0.5 MF, and 1.5 HF (%) to evaluate the fresh properties through slump flow, T500mm, V-funnel, L-box, and segregation tests. The results showed that all mixtures fell within the limits of EFNARC/2005. It was found that single and hybrid fiber addition reduces slump flow, L-box, and segregation, while the T500mm and V-funnel values increased. The hard properties of SLWSCC reinforced by fibers, such as compressive strength, flexural strength, splitting tensile strength, oven dry density, and water absorption were studied. The addition of fibers raises compressive, splitting tensile, and flexural strength, with the maximum augmentation of 21.4, 43.4, and 53.8%, respectively, occurring when adding 1 HF + 0.5 MF. The highest value of oven dry density was acquired when adding 1.5 MF and the highest water absorption rate was acquired after the addition of 1.5 HF.